Integrated ergonomic approach for residential chair design: A validation based on Malaysian anthropometry, RULA, and EMG - Amir Mohamed, Kamarul; Lee, Brenda Kar Mun; Yaakob, Mohd Yuhazri; Wan Mahmood, Wan Hasrulnizzam; Mohamed Noor, Ahamad Zaki; Syaifoelida, Fevi (Institute of Mechanics of Continua and Mathematical Sciences, 2025)
This study presents the design and evaluation of an ergonomic chair developed for Malaysian residential users through the integration of anthropometric data, ergonomic assessment, and experimental validation. Anthropometric dimensions from the Malaysian Anthropometric Database were applied to determine seat height, depth, width, and backrest dimensions suitable for local body proportions. Rapid Upper Limb Assessment (RULA) was conducted using digital manikins representing the 5th, 50th, and 95th percentiles to identify postures with minimal musculoskeletal risk. A 3D CAD model was created in SolidWorks, and finite element analysis (FEA) was performed to evaluate structural integrity under a 150 kg load. A full-scale prototype was validated using electromyography (EMG) testing involving 20 participants of varying height, weight, and body mass index (BMI). Root Mean Square (RMS) values of muscle activation were analyzed to assess comfort and fatigue. Results showed a RULA score of 2, strong structural stability, and low EMG activity, indicating minimal muscle strain. The integration of anthropometry, simulation, and EMG validation confirms the chair’s ergonomic suitability and establishes a framework for locally optimized furniture design.